Correction: Surface modification and endothelialization of biomaterials as potential scaffolds for vascular tissue engineering applications. (7th July 2015) - Ren, Xiangkui; Feng, Yakai; Guo, Jintang; Wang, Haixia; Li, Qian; Yang, Jing; Hao, Xuefang; Lv, Juan; Ma, Nan; Li, Wenzhong
Abstract : Correction for 'Surface modification and endothelialization of biomaterials as potential scaffolds for vascular tissue engineering applications' by Xiangkui Ren et al., Chem. Soc. Rev., 2015, DOI: ; Web:10.1039/c4cs00483c .